Custom foot orthoses for chronic metatarsalgia: Study protocol for a participant- and assessor-blinded superiority randomized controlled trial - Eléna Payen Schalkens; Maxime Acien; Andrée-Anne Marchand; Pier-Luc Isabelle; Jacques Abboud; Gabriel Moisan (PLoS ONE, 2026)
Background Chronic metatarsalgia (CM) causes significant pain and disability, affecting quality of life. Foot orthoses (FOs) including medially wedged designs with a metatarsal pad decrease excessive plantar pressure under the metatarsal heads, which is a suggested risk factor for developing CM. This FOs model may be effective in diminishing pain and improving function in these individuals. Thus, the objective of this trial will be to compare the effects of medially wedged FOs with a metatarsal pad and sham FOs on pain and foot function in individuals with CM. Methods/design This participant- and assessor-blinded superiority randomized controlled trial (RCT) with two parallel groups will be conducted in Trois-Rivières, Canada. Sixty-four participants with CM will be recruited from the Université du Québec à Trois-Rivières outpatient podiatry clinic and via social media invitations. They will be randomized into intervention (customized FOs) or control (sham FOs) groups and will be evaluated at baseline and after 6 and 12 weeks. The primary outcome will be: (1) mean pain during walking for the most painful foot during the past week. The secondary outcomes will be: (1) Foot Function Index, (2) Global rating of change and (3) the 5-level EQ-5D. Discussion Medially wedged FOs with a metatarsal pad are expected to provide a greater reduction in pain and improvement in foot function compared to sham FOs. This trial will help guide FOs prescription recommendations for managing foot pain in individuals with CM in the future. Trial registration ClinicalTrials.gov NCT06962475